Electrolyte materials for intermediate-temperature solid oxide fuel cells - Shi, Huangang; Su, Chao; Ran, Ran; Cao, Jiafeng; Shao, Zongping (Progress in natural science, 2020)
Solid oxide fuel cells (SOFCs) directly convert chemical energy that is stored in a wide range of fuels into direct current electricity, with high efficiency and low emissions, via a series of electrochemical reactions at elevated operating temperatures (generally 400–1000 °C). During such an energy conversion process, the properties of electrolyte materials determine the working principle and operating temperature of the SOFC. When considering the cost and stability, lowering the operating temperature is critical, and this has become one of the developing trends in SOFC research. The key point for realizing a reduction in operating temperature is to maintain low ohmic resistance of the electrolyte and low polarization resistance of the electrodes. In practice, the mechanical and chemical stability of the electrolyte is also a big concern. According to their differences in ion conduction mechanisms, there are three main types of electrolyte material available, namely, oxygen ion-conducting, proton-conducting, and dual ion-conducting electrolytes. In this review, we give a comprehensive summary of the recent advances in the development of these three types of electrolyte material for intermediate-temperature SOFCs. Both conductivity and stability are emphasized. In conclusion, the current challenges and future development prospects are discussed. [Display omitted] •The basic information for electrolyte materials for SOFCs are summarized.•The latest development in electrolyte materials for SOFCs are reviewed.•The challenges and prospects for development of electrolyte materials for SOFCs are discussed.